On regional modeling of the main geomagnetic field - Verbanac, Giuliana (Array, 2007)
Abstract: In this study I applied Spherical Cap Harmonic Analyses, SCHA, with physical regularization (Korte and Holme, 2003) to synthetic series obtained from the Comprehensive model CM4 (Sabaka et al., 2004), at 46 European observatory locations and additionally 11 'virtual observatories' chosen to improve the initial data distribution. The main purpose was to find an approach for minimising the known drawbacks of SCHA, and to test different effects on the model results, in order to get a tool which allows a better representation of the geomagnetic main field and its secular variation over restricted areas, as Europe is.I also show that an adequate selection of model parametrisation (spherical cap angle, maximal spherical cap harmonics order, number of splines, norms) and a physical regularization allow that model smoothness and misfit are those required by the data themselves.The misfit of the final model was tested using different criteria: the rms values, the time evolution of the coefficients and the behaviour of the original versus modeled time series at each location.Models computed for different epochs satisfy the proposed validation criteria, underlining the reliability to compute stable models over the whole considered time span. This study opens a way to describe in detail regional geomagnetic main field and its secular variation